Beliefs about sensitive parenting among mothers of children with disabilities - Matoso, L.; Baião, R.; Baptista, J. (Journal of Intellectual Disabilities, 2022)
The relevance of the quality of parent-child interactions for child development has long been established. Nevertheless, research on beliefs about maternal sensitivity is still scarce, to an even greater extent in the context of child disability. This inquiry aimed to describe beliefs about sensitive parenting among mothers of children with developmental disabilities and to examine how those beliefs relate to sociodemographic factors and perceived stress. Participants included 40 mothers with a child up to 7 years of age with a developmental disability. Mothers reported on sociodemographic factors and daily hassles and sorted an adapted version of the Maternal Behavior Q-Sort. Results revealed a strong convergence between maternal beliefs about the ideal mother and the attachment theory’s concept of sensitivity. Daily hassles predicted beliefs about the ideal mother. These results underline the importance of implementing interventions in the context of child disability aimed at reducing parental stress.